The dose-dependent efficacy of esketamine in spinal surgery with intraoperative neuroelectrophysiological monitoring: a randomized controlled trial - Lin, Chunyan; Wang, Jianlin; Zhang, Long; Yuan, Liyong; Liu, Guanyi; Zhu, Miao; Zhang, Liangguang (Frontiers in Medicine, 2025)
PurposeThis study aims to validate the efficacy and safety of combining different doses of esketamine with propofol, remifentanil, and dexmedetomidine in spinal surgery under intra-operative neuroelectrophysiological monitoring (IONM).MethodsAll enrolled patients underwent a total intravenous anesthesia (TIVA) maintenance regimen, which included propofol, remifentanil, and dexmedetomidine. The patients were randomly assigned to four groups based on the use and dosage of esketamine: Group Control (TIVA + NS), Group A (TIVA + Esketamine 0.1 mg/kg/h), Group B (TIVA + Esketamine 0.3 mg/kg/h), and Group C (TIVA + Esketamine 0.5 mg/kg/h). The study measured vital signs, consumption of anesthetics, operation time, blood loss, awakening time in the postanesthesia care unit (PACU), visual analog scale (VAS) pain score, quality of recovery (QoR) -15 score, and dosage of supplementary analgesics. Additionally, adverse postoperative reactions were recorded.ResultsGroup B had lower dosages of propofol (P = 0.021), remifentanil (P = 0.001), and dexmedetomidine (P < 0.001) than the Control Group, while Group C had lower dosages of remifentanil and dexmedetomidine (P < 0.001) than the Control Group. The postoperative mean arterial pressure (MAP) was lower in Group B than in the Control Group (P = 0.028). Patients in Group C experienced a prolonged awakening time (P < 0.001) but had lower VAS pain scores at PACU than those in the Control group (P = 0.044). Both QoR-15 scores and MoCA scores were significantly higher for patients in Groups A, B, and C compared to those of the Control group (QoR-15: P = 0.001, < 0.001, < 0.001; MoCA: P = 0.004, < 0.001, < 0.001). Group B had few postoperative complications.ConclusionThe dose of 0.3 mg/kg/h esketamine is safe and effective for spinal surgery with IONM, improving control of postoperative complications.